The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.20961/ijpte.v1i2.14534
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural and Intercultural of Indirectness Speect Act: The Use of Interference Local Language in Academic Discourse at Central of Sulawesi

Abstract: Cross-cultural and intercultural communication is a cross-ethnic communication that naturally arises in a social context with different religious, social, ethnic, and linguistic backgrounds. In this case, it is learned how people with different cultural backgrounds interact with each other using their language. One form of communication can be seen from the use of speech acts and the form of interference from the communicant language. This paper aims to describe how the use of Malay Manado local language inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Another research on educational podcasts by Drew (2017) found that genre analysis is helpful in introducing ideas resulting from illocutionary acts produced in an educational context. Additionally, different cultures used Commissive acts at different rates, with collectivist cultures using Commissive acts more frequently than individualistic cultures, as found in a cross-cultural study by Kasim et al (2017) and Taguchi et al (2016). In this respect, the results in question highlight the role of context, genre, topic, and cultural differences in analyzing how illocutionary acts are used in various contexts.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Another research on educational podcasts by Drew (2017) found that genre analysis is helpful in introducing ideas resulting from illocutionary acts produced in an educational context. Additionally, different cultures used Commissive acts at different rates, with collectivist cultures using Commissive acts more frequently than individualistic cultures, as found in a cross-cultural study by Kasim et al (2017) and Taguchi et al (2016). In this respect, the results in question highlight the role of context, genre, topic, and cultural differences in analyzing how illocutionary acts are used in various contexts.…”
Section: Introductionmentioning
confidence: 82%
“…In contrast, a study by Irwandika (2021) found that expressive acts-like expressing one's thoughts and feelings-were more common in online dialogues than compliant ones in social media communication. Moreover, Kasim et al (2017) researched the use of illocutionary actions in crosscultural communication and revealed that cultural differences affected the frequency and types of illocutionary acts employed, with variances in the usage of representatives and directions between cultures. Another research on educational podcasts by Drew (2017) found that genre analysis is helpful in introducing ideas resulting from illocutionary acts produced in an educational context.…”
Section: Introductionmentioning
confidence: 99%
“…Besides speaking courses, it also supports the students in learning the Cross-Cultural Understanding course taught in the fifth semester. This course examines the relationship between language and culture, the importance of understanding culture in studying a foreign language, personal values, culture's importance in second and foreign language learning, multiculturalism, and diversity (Kasim, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The specialness of women's refusal acts can also be seen in academic discourse context of female undergraduates in Central Sulawesi using a local language as a heritage language and language use. The variety of studies on speech acts in academic discourse becomes more important and interesting due to its continuity and synergy towards the previous study done [3]- [5] In the international level, similar research which studies on speech acts, gender, and ethnography of communication has been done [6]- [9] as well as on wide and multi-context scope the past research [10]. The refusal acts on spoken academic discourse by the ethnicity of Kaili, Buginesse, and Manado in Central Sulawesi is shaped by the use of body language, sign language, implicit meaning, and the traits of the local accents and dialects themselves.…”
Section: Introductionmentioning
confidence: 96%